Rancang Bangun Purwarupa Alat Penyanitasi Tangan Menggunakan Sensor Ultrasonik Berbasis Arduino - Unggul Boy Natanail; Yoga Listi Prambodo; Mega Tri Kurnia (FIKOM Universitas Bung Karno, 2023)
Hands are one of the potential mediums for viruses to enter the body during daily activities, so handwashing is one way to prevent the entry of viruses into the body. Using a hand sanitization device is one alternative. An automatic hand sanitization device can be useful in encouraging people to wash their hands without having to touch the device itself, which is usually done manually by pressing to dispense the soap. By planning and creating an automated hand sanitization system based on Arduino integrated with an ultrasonic sensor, this provides a solution to detect objects around the container. Consequently, the servo motor component will work automatically as a lever presser on the soap container pump. The hand sanitization device is programmed using simple instructions, and its performance will help the community prevent the entry of viruses by cleaning their hands after activities without having to touch the soap container.